Analisis Pengaruh IPM dan Angkatan Kerja Terhadap Kemiskinan di Kabupaten Tapanuli Utara - Pane, Putri Marito; bangun, Belliyani Br; Saragih, Putri Damayanti; Padang, Nova Romadiah; Simanjuntak, Lola Vitaloka; Umar, Andi Taufiq (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the effect of the Human Development Index (HDI) and the Labor Force on the poverty rate in North Tapanuli. The analysis method used is multiple linear regression. The data used in this study are secondary data obtained from the BPS (Central Bureau of Statistics) of North Tapanuli Regency from 2012 to 2023. The analysis results show that the regression model Y=66.713-0.821+1.866 Labor Force meets the classical assumptions and has a correlation coefficient (R) of 0.919 and a coefficient of determination (R2) of 0.810. Partially, the HDI variable has a significant negative effect on the poverty rate, while the Labor Force variable has a positive but not significant effect. Simultaneously, the HDI and Labor Force variables have a significant influence on the poverty rate in North Tapanuli. Keywords: Poverty, HDI, Labor Force